Evaluation of Hybrid Learning Programs in Higher Education: A Systematic Literature Review Approach - Fahriansyah, Faisal; Agustini, Ketut; Suradika, Suradika; Putra, Anak Agung Adi Wiryya (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This a This evaluation is expected to provide strategic advice on how to develop policies and learning practices in universities to maximize the benefits of hybrid learning and improve the quality of education. The aim of this study is to evaluate the effectiveness of hybrid programs that combine face-to-face and online methods. This research method uses literature review research. Effective learning systems can be applied in universities, the results of a literature review of several articles. Over the past four years, the hybrid model has developed and gained positive values from students. Universities use technology to meet the needs and learning styles of students.
Keywords: Literature Review; Evaluation of Hybrid Learning; Education